Pengembangan Aplikasi Pengenalan Kuliner Dan E-Recipe Khas Kalimantan Tengah Berbasis Android - Minarni Minarni; Nurani Aisiyah Tanjung; Nadia Sari; Nindi Ernawati (STMIK Budi Darma, 2022)
The culinary specialties of an area are part of local wisdom that must be preserved. Central Kalimantan with its cultural customs and local craftsmanship which is still very high has a variety of culinary delights with unique and interesting tastes and appearances. The problem that occurs is that the younger generation now knows more about European-style foreign cuisine and other foreign countries so that when asked about the local cuisine, not many people know about it. The culinary introduction along with its recipes aims to introduce as well as maintain and preserve these recipes so that they can still be passed on by the younger generation, especially the local people of Central Kalimantan. Along with the times, Android-based applications are in great demand among young people because of the various features that make it easy and enough to download the application on the Play Store. This application is named e-Recipe Cullinary KalTeng. The user interface of this application is designed using Figma and developed using the Flutter Platform with the Dart programming language. Features in this application include dishes and snacks typical of Central Kalimantan, each of which is also listed as a recipe. This application is tested using Black Box and the results show that the entire application can run well and is user friendly